Strategic Leadership Patterns and their impact on Innovation Performance: An analytical study at the Ministry of Interior - Ali, Salim Taha; Alnuaimy, Salah Abdel Qader (The journal of contemporary issues in business and government, 2021)
The Purpose of current research to test the effect of Strategic Leadership Patterns as an independent variable in the innovation performance as a dependent variable, in the Baghdad Intelligence and Counter-Terrorism Directorate of the Ministry of Interior, and then try to come up with a set of recommendations that contribute to enhancing the innovation performance of the researched organization. And based on the importance of the research topic in the researched organization, and the importance of the research organization to society, a descriptive-analytical approach was adopted in its achievement, and the research was applied in the Intelligence and Counter-Terrorism Directorate in Baghdad, and the research targeted an intentional quota sample of leaders and military ranks, and data were collected from (145) respondents representing a community. The research is exclusively and comprehensive, represented by (director of the directorate, assistant director of the directorate, directors of departments, assistants of department directors, divisional directors, unit officials), by adopting the questionnaire that included (45) paragraphs, and using personal interviews and field observations as tools to help in collecting them. The research adopted the program (Amos V.25, Spss V.26) with the adoption of descriptive statistical methods (linearity test, normal distribution test, confirmatory factor analysis, building variables models, arithmetic mean, percentages, standard deviation, relative importance, coefficient of variation, And the correlation coefficient (Pearson coefficient, and the simple and multiple regression coefficients) to test its hypotheses, and the research concluded the most prominent result represented in the validity of its hypotheses, the existence of a positive positive effect of strategic leadership patterns on innovation performance, as well as the availability of the two variables, practice, interest, and adoption.